Systematic Literature Review: Dysfunctional Auditing, Time Budget Pressure, and Audit Quality in APIP - Tupanno, Putri Neira Ar; Djaddang, Syahril (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The Government Internal Supervisory Agency (APIP) plays a vital role in ensuring state financial accountability, in line with the principles of Stakeholder Theory, which demands accountability to the public. However, the quality of APIP audits is threatened by job demands in the form of time budget pressure (TBP) and budget efficiency requirements. This double pressure is the main trigger for the emergence of Auditor Dysfunctional Behavior (PDA), which is a key mediator of declining audit quality. Therefore, this Systematic Literature Review (SLR) was conducted to map the causal path between work pressure, PDA, and Audit Quality, as well as to evaluate the mitigating role of Job Resources (JR) in the context of APIP. Objectives & Methods: The main objectives of this SLR are to analyze and synthesize empirical literature on (1) the influence of TBP and Budget Efficiency on PDA, (2) the mediating role of PDA on Audit Quality, and (3) the moderating role of JR in the relationship between PDA and Audit Quality. The method used is SLR with reference to the PRISMA guidelines. The literature search was limited to empirical articles in Indonesian and English published in the last five years (2020–2025). Key Findings: The synthesis results show that TBP and Budget Efficiency have a positive and significant relationship with an increase in PDA. PDA has been consistently proven to act as a strong mediating variable, substantially weakening Audit Quality. Furthermore, the findings indicate that Job Resources (such as supervision and training) have critical potential as moderating variables, capable of weakening the negative relationship between PDA and Audit Quality, although findings regarding this moderating mechanism still vary across studies. Implications: Theoretically, this SLR strengthens the integration of JD-R Theory and Stakeholder Theory, providing a comprehensive framework for understanding internal auditor behavior. Practically, this study recommends that APIP leaders design more proportional policies in time and budget allocation, as well as increase investment in Job Resources (e.g., supervision and professional development systems) to minimize PDA and maintain Audit Quality as the highest form of accountability to all public stakeholders.